1969
DOI: 10.1111/j.1365-3180.1969.tb01471.x
|View full text |Cite
|
Sign up to set email alerts
|

INCORPORATED VERSUS SUBSURFACE VERNOLATE FOR WEED CONTROL TN PEANUTS*

Abstract: Summary. Under dry field conditions, vernolate (S‐propyl dipropylthiocarbamate) incorporated by conventional methods controlled less yellow nutsedge (Cyperusesculentus L.) and injuied peanuts (Arachis hypogaea L., groundnuts) more than when injected in lines under the soil or subsurface‐applied through sweep applicators. In glasshouse studies, vernolate eliminated production of new nutsedge tubers if it was applied below the soil surface either 1 in. above or 1 in. below the parent tuber. Method of placement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1971
1971
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…No explanation can be given for the aberration. Previous research (10,12,14) has indicated that vemolate will control yellow nut sedge early season very well, but is less effective as the growing season progresses.…”
Section: Resultsmentioning
confidence: 98%
“…No explanation can be given for the aberration. Previous research (10,12,14) has indicated that vemolate will control yellow nut sedge early season very well, but is less effective as the growing season progresses.…”
Section: Resultsmentioning
confidence: 98%
“…Because the 3.8-cm band was more effective than the 7.6-cm band, possibly the optimum band placement is less than 3.8 cm for this weed in this soil. On the other hand, Hauser et al (6) have reported that, under dry conditions, yellow nutsedge was controlled better by banded vernolate than by incorporated treatments. Our results show young plants are easier to kill than old plants.…”
Section: Discussionmentioning
confidence: 98%
“…Hauser et al (6) reported that vernolate incorporated in the soil controlled yellow nutsedge (Cyperus esculentus L.) less and injured peanuts (Arachis hypogaea L.) more than verno-late applied as an injected or subsurface soil treatment. The average yield of peanuts (2 yr on two soil types) was 14% greater after subsurface application of vernolate than after in corporation of vernolate.…”
Section: Introductionmentioning
confidence: 99%